Improving Learning Outcomes and Motivation Theme VI Sub Theme 2 Using the Problem-Based Learning Learning Model for Grade IV Students at SD Negeri Banjarsari Samigaluh 2021/2022 Academic Year - Puji Lestari (Universitas Islam Indonesia, 2023)
This study aims to improve student learning outcomes and motivation by using the problem-based learning (PBL) model in theme VI, sub-theme 2 class IV of SD Negeri Banjarsari Samigaluh for the 2021/2022 academic year. This type of research is Classroom Action Research which was carried out for 2 cycles, each cycle consisting of 2 meetings. The subjects in this study were fourth-grade students at SD Negeri Banjarsari Samigaluh, totaling 8 students consisting of 6 boys and 2 girls. Data collection techniques in this study used observation and then the data were analyzed descriptively and presented in tabular form. The results obtained in this study showed a significant increase in student learning outcomes, wherein the first cycle students who met the Minimum Completeness Criteria obtained an average score of 4.5 with a percentage of 56.25% while in the second cycle of the participants students who meet the Minimum Completeness Criteria obtain a score of 7.5 with a percentage of 93.75%. In cycle I to cycle II it is known that the learning outcomes of students have increased by 36.50%. As for the observational data on students' learning motivation objects also showed a significant increase, where in cycle I an average value was obtained of 3.6 with a percentage of 71.19% and in cycle II an average value was obtained of 4.3 with a percentage of 85.20%. This shows that from cycle I to cycle II, students' learning motivation increased by 14.01%. Therefore, it can be concluded that the application of the problem-based learning (PBL) learning model to theme VI, sub-theme 2 can improve the learning outcomes and motivation of fourth-grade students at SD Negeri Banjarsari Samigaluh in the 2021/2022 academic year.